Magnetoresistance of Nanoscale Domain Walls Formed in Arrays of Parallel Nanowires - Shvets, Igor (My University, 2019)
We present the possibility of enhancing magnetoresistance by controlling nanoscale domain wall (DW) width in a planar nanowire array. Results based on the micromagnetic calculations show that DW width decreases with increasing exchange bias field and decreases with reducing exchange interaction between neighboring nanowires. Fe/Fe3O4 nanowire arrays were grown on c-plane sapphire to demonstrate the feasibility of this concept, and an enhanced MR ratio of 3.7% was observed at room temperature.
Keywords: Magnetoresistance; Nanowire arrays